English Teaching Strategies For Young Learners In Bilingual Elementary Classes In An EFL Context - Andita Sayla Purnawati; Pasca Kalisa (Universitas Pahlawan Tuanku Tambusai, 2026)
Effective English instruction in bilingual elementary settings is critical for developing young learners’ language competence alongside content knowledge. However, empirical studies on English as a Medium of Instruction (EMI) at the primary level in EFL contexts remain scarce, particularly those documenting actual classroom practices. This study aims to explore English teaching strategies employed by teachers in bilingual elementary classrooms in Indonesia. A descriptive qualitative design was employed, involving two English teachers and one subject teacher selected through purposive sampling. Data were collected via classroom observation, semi-structured interviews, and document analysis, then analyzed using reflexive thematic analysis. The findings reveal six interconnected strategies: routinized English exposure, activity-based instruction, scaffolding, code-switching, differentiated instruction, and curriculum alignment. These strategies function in an integrated, context-sensitive manner adapted to learners’ developmental stages. The study concludes that effective bilingual elementary instruction requires flexible, student-centered approaches that simultaneously support language acquisition and content comprehension.